Dinamika Wacana Kemiskinan dan Implementasi Program Keluarga Harapan di Kota Makassar: Perspektif Sosial dan Politik - Mario Mario (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2025)
. Poverty is a multidimensional problem that is not only related to economic aspects but also social and cultural. The Family Hope Program (PKH) in Makassar City is implemented as an effort to empower poor families through conditional assistance that requires active participation of recipients in fulfilling their children's education and health obligations. This study aims to analyze the construction of poverty discourse in the implementation of PKH, discourse contestation between social actors, and its impact on participation and legitimacy of the program. The research method used is qualitative with a descriptive approach, involving in-depth interviews and participatory observations of 15 beneficiaries and 3 social assistants in Makassar. The results of the study show that the official discourse of poverty based on administrative data often ignores the complexity of the experiences of the poor, thus giving rise to resistance and the emergence of counter-discourses that demand recognition of local narratives. This contestation has an impact on the limited space for dialogue and community participation, which results in the social legitimacy of PKH becoming fragile. Social assistants play an important role in facilitating inclusive communication and empowerment of beneficiaries, increasing their sense of ownership and active participation. In conclusion, the success of PKH is highly dependent on the transformation of poverty discourse to be more responsive and inclusive, strengthening the capacity of facilitators, and building a participatory deliberative public space to strengthen the legitimacy and effectiveness of the program.